Enhanced photocatalytic and antifungal activity of ZnO–Cu2+and Ag@ZnO–Cu2+ materials. Issue 9 (1st May 2022) - Medina-Ramírez, Iliana E.; Marroquin-Zamudio, Adriana; Martínez-Montelongo, Jorge H.; Romo-Lozano, Yolanda; Zapien, Juan Antonio; Perez-Larios, A.
Abstract: Zinc oxide is one of the most versatile nanostructured materials with a broad range of applications. Besides, its physicochemical properties can be tuned easily by synthesis conditions to be optimal for a specific application. In our group, we aim for the production of visible light-active materials with enhanced antimicrobial activity. Thus, we synthesize ZnO–Cu 2+ and Ag@ZnO–Cu 2+ by using a fast and robust microwave solvothermal reaction. We investigate the limit of solubility of Cu 2+ into ZnO lattice producing Cu doped ZnO materials with different doping levels (1, 2, 3, 4, and 5 at. %, Cu/Zn). We also investigate the role of the copper precursor, using copper(II) acetate or copper(II) sulfate as model precursors. Copper acetate incorporates more efficiently into ZnO lattice by decreasing the Eg value of the doped materials at low doping levels. Furthermore, we study the composites Ag@ZnO–Cu 2+ aiming to reduce doping levels and to improve antimicrobial activity. Characterization of the materials by different techniques demonstrates their uniform size, purity, crystallinity, and visible light activity. In this study, we evaluate airborne fungal contamination and demonstrate the capacity of ZnO–Cu 2+ and Ag@ZnO–Cu 2+ to inhibit fungal growth. We studied the microbiological quality of indoor air (vivarium) by sampling air under different conditions. By sampling air with a photocatalytic prototype, the amount of fungi in the air decreases considerably, particularly fungi that can enter the lung. In addition, ZnO–Cu 2+ shows excellent antifungal activity against Candida sp at low doses. We use Atomic force microscopy (AFM) and holotomographic microscopy (HTM) to provide further evidence on the capacity of the prepared materials to achieve effective damage to fungal cells and to inhibit biofilm formation. Graphical abstract: Image 1 Highlights: ZnO–Cu 2+ materials were synthesized using different Cu(II) precursors and Cu doping levels. Incorporation of Cu(II) dopant within ZnO matrix is favored using Cu(II) acetate as precursor. The materials exert excellent antifungal activity at low doses (0.3 mg/mL) and short exposure times (5 h). Supported ZnO–Cu 2+ materials are indoor light active catalyst with outstanding capacity for the disinfection of indoor air. The antifungal capacity of materials demonstrated by classical microbiology assays and advanced microscopy studies.